ASYMPTOTIC NORMALIZATIONCOEFFICIENTS FOR 24Mg+p→25Al AND THEIR APPLICATION TO NUCLEAR ASTROPHYSICS - Ikromxonovov, E.Sh.; Tojiboev, O.R.; Karomov, Y.K. (Educational Research in Universal Sciences, 2023)
Nowadays in the world a lot of attention is drawn again to obtaining reliable information about the structure of the low-lying nuclear states (Spectroscopic factor, asymptotic normalization coefficient (ANC)). In addition to important information on the structure of nuclei, the ANC values are widely used to calculate the cross sections (S factors) and rates of reactions of radiative nucleon capture in stellar medium. The aim of this dissertation work, is to determine the ANC value for the single-particle bound state of 25Al→24Mg+p from the analysis of the experimental differential cross section of the proton transfer 24Mg(3He,d)25Al reaction. This value is important for estimating the astrophysical S-factor for radiative capture of the proton by the 24Mg nucleus, which is the first link in the MgAl chain of the 24Mg(p,γ)25A1(β+)25Mg(p,γ)26A1(β+)26Mg cycle.